The Impact of Working Capital Management on Profitability: Evidence from Non-Financial Firms Listed in NEPSE - Shrestha, Purna Man (Journal of Innovation in Academia, 2023)
Efficient working capital management (WCM) is expected to contribute positively to the firm’s profitability. With the aim of analyzing the impact of WCM on the profitability of non-financial firms listed in NEPSE, this paper has used current ratio (CR), debt ratio (TDTA), current assets to total assets (CATA), current liabilities to total assets ratio (CLCA) and inventory conversion period (ICP), receivable conversion period (RCP), payable deferral period (PDP), and cash conversion cycle (CCC) as the measures of WCM. This paper has used annual panel data of 12 non-financial NEPSE-listed firms from 2005/06 to 2019/20. Based on the result of the Breusch and Pagan Lagrangian multiplier and Hausman tests, the study found the Random Effect model as the appropriate regression model. Using the Random Effect regression model, this paper has found the significant impact of WCM on profitability. Likewise, this paper found a significant negative impact of the current ratio (CR) and debt ratio (TDTA) and a significant positive impact of the ratio of current assets to total assets (CATA) on profitability. Further, the finding also reveals that there is an insignificant negative impact of the inventory conversion period (ICP) and receivable conversion period (RCP) and an insignificant positive impact of the payables deferral period (PDP). Thus, this paper concludes that Nepalese non-financial firm can increase their profitability by decreasing the current ratio (CR) and debt ratio (TDTA) and increasing the ratio of current assets to total assets (CATA).